Calorie Intake and Poverty Levels in Andhra Pradesh with Special Reference to Srikakulam District - G. , Appala Naidu (International Journal of Psychosocial Rehabilitation, 2020)
In this paper, an attempt is made to analyze the calorie intake and poverty levels in the study area. The present study is conducted in Srikakulam Dist. in Andhara Pradesh. The study covers two mandals, viz., Polaki and Etcherla Mandals in Srikakulam District, for the purpose of calculating calorie intake and poverty levels. The results of the average per capita calorie intake per day revealed that it is lower (i.e., 3599.40) in Etcherla mandal when compared to Polaki mandal (i.e., 3817.56). The results of sub-castes revealed that the average per capita calorie intake per day is lower in STs and SCs when compared to BCs and OCs in both the mandals. From this it may be inferred that the heads of the households should be motivated to change the pattern of allocation of expenditure by shifting the expenditure made on alcoholic consumption to consumption of calorie intake. The analysis of the distribution of households according to Head Count Ratio (HCR) revealed that 30% of the households are lying below the poverty line (BPL) in Etcheral mandal, while it is 27% of households in Polaki mandal. However, the analysis of sub-castes revealed that in both the mandals, the majority of the people belonging to SC and ST groups are lying below the poverty line. From this it may be inferred that, though the government has been launching several poverty alleviation programs, these are not adequate to wipe out poverty in the society. This may be the reason that the government is undertaking special programs to extend the benefits of the fruits of development to the weaker sections in the name of “inclusive growth” during the Eleventh Five-Year Plan.